Барселонская галерея: [роман] / Олег Рой - Рой Олег Юрьевич (Капризы судьбы, 2009)
Экземпляры: ф. 1 (20091008) / Инвентарный номер: 94957 / Цена: 126.70 / Авт.знак: Р 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6